"When" and "why" employees resort to remain silent at work? A moderated mediation model of social undermining. Issue 3 (14th March 2022) - Xu, Aidi; Ayub, Arslan; Iqbal, Shahid
Abstract : Purpose: To date, few empirical studies have explored the boundary conditions under which employees may choose to observe silence at work. Drawing on the conservation of resource (COR) theory, the present study bridges this gap by examining the interaction effect of leader-member exchange (LMX) on the relationship between social undermining and employee silence while considering the mediating role of emotional exhaustion. Design/methodology/approach: Data were collected from 327 employees working in Pakistan's service sector through the purposive sampling technique and analyzed using PLS path modeling. Findings: The findings support the authors' projections such that social undermining, i.e., supervisor undermining, coworker undermining and customer undermining, are positively related to emotional exhaustion. Besides, emotional exhaustion partially mediates the associations between supervisor undermining and employee silence, coworker undermining and employee silence, and customer undermining and employee silence. Further, the results confirm the interaction effect of LMX. The harmful impact of social undermining is exacerbated in high-quality LMX relationships compared to those at low LMX relationships. Originality/value: This study is one of the few efforts to understand the conditions under which employee silence is more likely or less likely to occur. The authors' findings draw the attention of researchers and practitioners to understand the uniqueness of this linkage such that variations in leaders' behavior are more detrimental for "in-group" members than their counterparts (i.e. "out-group" members).